2009
DOI: 10.1097/sla.0b013e3181b248bb
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Genes Associated With Malignant Pheochromocytomas by Genome-Wide Expression Profiling

Abstract: Differentially expressed genes between benign and malignant pheochromocytomas distinguish between these tumors with high diagnostic accuracy. Our findings provide new insight into the genes and molecular pathways that may be involved in malignant pheochromocytomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Brouwers et al 38 examined 20 malignant tumors along with 70 sporadic and syndromic benign tumors: Gene Ontology Analysis of benign and malignant tumor comparison revealed the relevance of signal transduction changes. The significant gene sets established in two recent large-scale studies by Thouënnon et al 39 and Suh et al 40 are quite different, which indicates the need for further, large-scale gene expression profiling studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Brouwers et al 38 examined 20 malignant tumors along with 70 sporadic and syndromic benign tumors: Gene Ontology Analysis of benign and malignant tumor comparison revealed the relevance of signal transduction changes. The significant gene sets established in two recent large-scale studies by Thouënnon et al 39 and Suh et al 40 are quite different, which indicates the need for further, large-scale gene expression profiling studies.…”
Section: Discussionmentioning
confidence: 95%
“…Transcriptomic studies representing targets of miRNA-based regulation are pivotal for the correct interpretation of miRNA findings. There have been six previous studies 11,[37][38][39][40][41] on gene expression profiling involving malignant pheochromocytomas to date. The studies of Dahia et al, 11 Björklund et al 37 and the most recent study of Waldmann et al 41 included only two, three and five malignant pheochromocytomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we emphasize that the expression of aHIF is highly variable, so it cannot be used as a marker of malignancy in individual patients. It is likely that individual risks of developing metastases can only be estimated by the use of a combination of clinical, biochemical, genetic, and molecular markers (Eisenhofer et al 2004, Suh et al 2009. In this context, protein expression of SNAIL, a zinc-finger transcription factor, has been identified as a useful marker of metastatic potential of PGL (Häyry et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors can be diagnosed only after metastasis appearance (Kantorovich & Pacak 2010). Recent comparative microRNA and mRNA array studies made it possible to identify a set of genes that could discriminate benign from malignant tumors and to gain insights into the potential mechanisms underlying the occurrence of malignancy in pheochromocytomas (Thouënnon et al 2007, Suh et al 2009, Meyer-Rochow et al 2010, Waldmann et al 2010. In addition, we have demonstrated that EM66 levels increase significantly in the plasma of patients with pheochromocytomas (Guillemot et al 2006) and that low concentrations of this SgIIderived peptide in tumoral tissue are associated with malignancy (Yon et al 2003), indicating that EM66 may represent a valuable new diagnostic and prognostic marker of pheochromocytomas .…”
Section: Introductionmentioning
confidence: 99%